(3JJeI JcedI GdeMjWs - (3eMj GdOjf eMeO Hf jMji GdfjSGHhQj, GdNHhTGfj,J (B548 (3g` s ((3MeO Gddg Hf YeQ Hf TgGH GdcGRQhfi s)
(3BNQgG (B:s
(3GdHGH GdKGfi ai cjajI GdUQa Edi GdeSJMbjf ef cJGH bSe GdUObGJ s
(3GdeMjW TQM Hg cJGH GdhSjW dCSJGPg MLI GdESdGe GdZRGdi hCFeI HgPg GdJJeIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs